LEUCEMIE LYMPHOIDE CHRONIQUE (LLC) - BELGACEM, Nacéra; BOUCIF, Souhila (My University, 2021)
Chronic lymphoid leukemia is the most common leukemia in adults in the West, with a clear predominance of men. It results from proliferation with malignant monoclonal accumulation of mature B lymphocytes with invasion of the bone marrow, blood and other hematopoietic organs. the disease is linked as much to a lack of apoptosis as to excessive proliferation. The objective of this work is to study CLL chronic lymphocytic leukemia and the different diagnostic methods based on symptoms and prognostic factors. The importance of karyotype cytogenetic analysis and FISH for the detection of different chromosomal abnormalities to classify patients according to their unfavorable profile. Study molecular aspect of LLC and chromosomal abnormalities in particular the 17p13 deletion of the P53 gene.
Keywords: LLC: chronic lymphocytic leukemia, FISH, Karyotype, p53